A pesquisa-ação na formação continuada do professor em serviço: um estudo da prática docente no colégio Franciscano Sant´anna, Santa Maria, RS - Veiga, Célia de Fátima Rosa da (2015)
This thesis deals with the analysis of the teaching practices carried out by the methodological principles of action research. The study was conducted during the process of continuing education in service teachers of the schools of the Charitable Society and Literary Saint Francis of Assisi - SCALIFRA-ZN. The research investigated the teaching practices from the methodological principles of action research developed in the process of continuing education of the Sant'Anna School, analyzing their contribution to the qualification of practice in teacher education. The research is qualitative methodological nature, based on the principles of action research. The subjects of the study are elementary school teachers and High School. The theoretical basis of this study refer to Nóvoa (2009) Thiollent (2011), Pimenta (2011), Imbernon (2012), Franco (2012) among others. The data were produced making use of different tools and strategies, questionnaire, observations, records of the participants themselves and evaluation. Data analysis was performed by means of Laurence Bardin Content Analysis (2011). The study pointed to the importance of collaborative partnerships between educational manager and teacher; the pedagogical advice as systematic routine individual monitoring and collective; socialization of teaching experience and shared analysis of the practices, the development of evaluation culture in the school. The participating teachers of the research shows the reflexive action as a pedagogical innovation strategy and the continued training everyday with proactive actions in the school context. The use of action research framework turned out to provide and encourage changes mainly on aspects of school management and rethink ways and strategies that are offered and designed the continuing education practices in the school.